Los peligros de la industrialización. El caso del estanque del Pourra (1812-1846) - Xavier Daumalin (Amnis)
The shores of Fos-sur-Mer and the Étang-de-Berre have been confronted with the socio-economic and environmental effects of heavy industry for more than two centuries. The area has been dedicated to mixed farming, salt production, fishing and seaside activities for many years. Also for more than two centuries its residents have been concerned about, and openly and violently opposed the various pollutants linked to the plant activity more or less regularly. This text takes a look at one of the highlights of this across-the-centuries conflictual atmosphere – the Saint-Mitre villagers rioting in the first half of the 19th century –, its resources, challenges, what the power struggles and social inequalities operating in this territory also reveal, when dealing with illness, death and the various elements that make up its distinctiveness, or even its unusual character, in view of what we already know about similar conflicts that have happened in Provence and the rest of the world.